Design of a Plastic Shredder Machine - Nuri Aryani; Dede Buchori; Albertus Budi Setiawan (IPTEK Journal of Proceedings Series, 2019)
Waste is one of the problems that still unsolved especially for plastic waste. If the handling of plastic waste cannot be done well, it will have effect for the long period. The effect of plastic waste is environment problems such as: chain food disturb, contaminate ground water, air pollution, extinction anima, poisonous soil, and act. One of the handling for plastic waste is recycling. It starts with separating plastic waste by kind of plastic. The next step is crush it until it becomes small flakes. The Small flakes can be directly used for making product such as pot, filler material for mixing with road asphalt or plastic granulate for making a product by injection mold or extraction. In order to handle plastic waste into small flakes, plastic shredder can be used to realize the making of prototype of plastic shredder machine. It starts with design process. The design process of the prototype of plastic shredder machine uses the method of design Pahl and Beitz method that consists of design and describes job, design product concept, embodiment design, and design of detail. The plastic shredder machine consists of blades or cutter, transmission element with the shape of spur gear, electric motor, and body of machine. The kind of waste plastic for shred is LDPE, HDPE, PP, PSBased for the design of plastic shredder machine can produce small flake with the dimension of about 10 mm long and 1 mm wide.